Staff views on member participation in a mental health clubhouse. (2nd December 2018) - Chen, Fang‐Pei; Oh, Hans
Abstract: The clubhouse model is a community psychiatric rehabilitation program aiming to provide a restorative environment for people with severe mental health problems. These clubhouses provide their members with opportunities for friendship, employment, and education, which help them on their paths towards mental health recovery. Towards that end, the model features clubhouse members and staff working side by side to execute clubhouse activities. That is, unlike most of the community mental health programs where staff provide services to their clients, clubhouse staff are required to partner with members in their work. The aim of this qualitative study was to understand how the clubhouse staff elicited member participation and facilitate recovery. The research was conducted between Year 2013 and Year 2014 at the world's first clubhouse: Fountain House in New York City. The first author conducted 262 hr of active participant observation in 41 visits to Fountain House, and in‐depth interviews with 38 staff members who had worked at Fountain House for at least 1 month during the study period. The dimensional analysis procedure was used to analyse the observation notes and interview transcripts. Results showed that participation was a key to rebuilding members' self‐confidence, which further encouraged members to seek more opportunities for self‐enhancement and personal growth. Specific organisational policies, programming, practical considerations, and other strategies shaped a positive environment for members to exercise autonomy, experience self‐efficacy, and model behaviours after others who have succeeded. Findings of this research support the egalitarian staff–member relationships and the maintenance of an open and transparent atmosphere of the clubhouse, as observational learning enables members to move forward with their journeys to recovery. Findings also may inform efforts to shift traditional psychiatric services towards recovery‐oriented care.